Perioperative, short-, and long-term mortality related to fixation in primary total hip arthroplasty: a study on 79,557 patients in the Norwegian Arthroplasty Register - Dale, Håvard; Børsheim, Sjur; Kristensen, Torbjørn Berge; Fenstad, Anne Marie; Gjertsen, Jan-Erik; Hallan, Geir; Lie, Stein Atle; Furnes, Ove (Acta Orthopaedica, 2019)
Background and purpose — There are reports on perioperative deaths in cemented total hip arthroplasty (THA), and THA revisions are associated with increased mortality. We compared perioperative (intraoperatively or within 3 days of surgery), short-term and long-term mortality after all-cemented, all-uncemented, reverse hybrid (cemented cup and uncemented stem), and hybrid (uncemented cup and cemented stem) THAs. Patients and methods — We studied THA patients in the Norwegian Arthroplasty Register from 2005 to 2018, and performed Kaplan–Meier and Cox survival analyses with time of death as end-point. Mortality was calculated for all patients, and in 3 defined risk groups: high-risk patients (age ≥ 75 years and ASA > 2), intermediate-risk patients (age ≥ 75 years or ASA > 2), low-risk patients (age < 75 years and ASA ≤ 2). We also calculated mortality in patients with THA due to a hip fracture, and in patients with commonly used, contemporary, well-documented THAs. Adjustement was made for age, sex, ASA class, indication, and year of surgery. Results — Among the 79,557 included primary THA patients, 11,693 (15%) died after 5.8 (0–14) years’ followup. Perioperative deaths were rare (30/105) and found in all fixation groups. Perioperative mortality after THA was 4/105 in low-risk patients, 34/105 in intermediate-risk patients, and 190/105 in high-risk patients. High-risk patients had 9 (CI 1.3–58) times adjusted risk of perioperative death compared with low-risk patients. All 4 modes of fixation had similar adjusted 3-day, 30-day, 90-day, 3–30 day, 30–90 day, 90-day–10-year, and 10-year mortality risk. Interpretation — Perioperative, short-term, and longterm mortality after primary THA were similar, regardless of fixation type. Perioperative deaths were rare and associated with age and comorbidity, and not type of fixation.